Socialization of sailing safety for fishermen at Cituis Port - Prasetyo, Hendi; Asnawi, Asnawi; Irwansyah, Rudi Harun; Munawir, Ahmad; Setyawan, Deny Adi; Zulkarnain, Mokhammad; Shulhany, Ahmad; Ischak, Rabbani; Hidayatuloh, Ade Taopik; Sunanto, Hari; Widodo, Agus (Journal of Community Service in Science and Engineering (JoCSE), 2024)
This community service project, conducted by Politeknik Pelayaran Banten, focused on providing sailing safety counseling to fishermen at Cituis Port in Karang Serang village. The initiative sought to address the challenges faced by local fishermen by improving their awareness of safety practices, alleviating economic constraints, and mitigating the risks associated with navigating and operating in demanding marine environments. Through participatory workshops and practical demonstrations, fishermen were educated on effective safety practices and emergency responses. The distribution of life jackets further emphasized the importance of preparedness. The project also involved collaborating with local governments and organizations to enhance sustainability. By increasing safety awareness and equipping fishermen with critical resources, this program protected lives and fostered a safer and more resilient maritime community. This effort aligns with the institution's mission of contributing to sustainable marine development and community empowerment. Kegiatan pengabdian masyarakat ini, yang dilaksanakan oleh Politeknik Pelayaran Banten, bertujuan memberikan penyuluhan tentang keselamatan berlayar kepada para nelayan di Pelabuhan Cituis, Desa Karang Serang. Kegiatan ini dirancang untuk mengatasi tantangan yang dihadapi nelayan lokal dengan meningkatkan kesadaran mereka tentang praktik keselamatan, meringankan kendala ekonomi, dan mengurangi risiko yang terkait dengan navigasi serta operasi di lingkungan laut yang menantang. Melalui lokakarya partisipatif dan demonstrasi praktis, para nelayan diberikan edukasi tentang langkah-langkah keselamatan yang efektif dan respons darurat. Pembagian jaket keselamatan juga menjadi penekanan penting akan kesiapan menghadapi keadaan darurat. Proyek ini melibatkan kerja sama dengan pemerintah setempat dan organisasi terkait untuk memastikan keberlanjutan program. Dengan meningkatkan kesadaran keselamatan dan menyediakan sumber daya yang penting, program ini tidak hanya melindungi nyawa, tetapi juga membangun komunitas maritim yang lebih aman dan tangguh. Upaya ini selaras dengan misi institusi dalam mendukung pembangunan kelautan yang berkelanjutan dan pemberdayaan masyarakat.